Microstructure and strengthening mechanisms in an FCC structured single-phase nanocrystalline Co25Ni25Fe25Al7.5Cu17.5 high-entropy alloy - Fu, Zhiqiang; Chen, Weiping; Wen, Haiming; Zhang, Dalong; Chen, Zhen; Zheng, Baolong; Zhou, Yizhang; Lavernia, Enrique J. (Acta materialia, 2016)
We report on a study of the design, phase formation, microstructure, mechanical behavior and strengthening mechanisms of a novel single-phase Co25Ni25Fe25Al7.5Cu17.5 (at.%) high-entropy alloy (HEA). In this investigation, a bulk nanocrystalline (nc) Co25Ni25Fe25Al7.5Cu17.5 HEA with the face-centered cubic (FCC) crystal structure was fabricated by mechanical alloying (MA) followed by consolidation via spark plasma sintering (SPS). The X-ray diffraction (XRD) and transmission electron microscopy (TEM) results revealed that a single FCC solid-solution phase with an average grain diameter of 24 nm was produced following MA. Following SPS, bulk samples exhibiting a bimodal microstructure with both nanoscale grains and ultra-fine grains (UFGs) and with an average grain diameter of 95 nm were obtained, possessing a single FCC solid-solution phase identical to that in the milled powders. The single-phase feature of the Co25Ni25Fe25Al7.5Cu17.5 HEA principally resulted from remarkably high mutual solubility in most binary atom-pairs of the constituent elements, which appears to correspond to a high entropy of mixing. Approximately 5 vol.% of nanoscale twins were observed in the bulk nc samples. The bulk nc Co25Ni25Fe25Al7.5Cu17.5 HEA exhibits a compressive yield strength of 1795 MPa with a hardness of 454 Hv, which is dramatically higher than the yield strength of most previously reported FCC structured HEAs (∼130–700 MPa). Compared to those of the bulk coarse-grained (CG) Co25Ni25Fe25Al7.5Cu17.5 HEA fabricated by arc-melting, the yield strength and Vickers hardness values of the bulk nc samples increased by 834.9% and 251.9%, respectively. Quantitative calculations of the respective contributions from each strengthening mechanism demonstrate that grain boundary strengthening and dislocation strengthening are principally responsible for the measured ultra-high strength of the bulk nc Co25Ni25Fe25Al7.5Cu17.5 HEA. [Display omitted]